2009
DOI: 10.1007/s11663-009-9277-4
|View full text |Cite
|
Sign up to set email alerts
|

Gas Atomization of Amorphous Aluminum Powder: Part II. Experimental Investigation

Abstract: The optimal processing parameters that are required to atomize amorphous Al were established on the basis of numerical simulations in part I of this study. In this part II, the characterization of cooling rate experienced by gas-atomized, Al-based amorphous powders was studied via experiments. An experimental investigation was implemented to validate the numerical predictions reported in part I of this study. The cooling rate experienced by the powders, for example, was experimentally determined on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…The grain size decreased as the powder size decreased. Hong et al [10,16] proved that the average grain size depends linearly on the powder size and is proportional to the cooling rate of the powders. The fine structure of the powders benefits from the high rate of solidification of the gas atomization process, in which the crystallization process has been suppressed due to the large under-cooling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grain size decreased as the powder size decreased. Hong et al [10,16] proved that the average grain size depends linearly on the powder size and is proportional to the cooling rate of the powders. The fine structure of the powders benefits from the high rate of solidification of the gas atomization process, in which the crystallization process has been suppressed due to the large under-cooling.…”
Section: Resultsmentioning
confidence: 99%
“…One of the advantages of these particles is that they have a well-documented crystallographic orientation relationship [5,6] which provides high coherency, thus (1) acting as a nucleus during the solidification of Al [5]; and (2) lowering the solid-particle interfacial energy to improve particle engulfment during solidification [6]. Besides, previous works have proved that the rapid solidification process and the decrease of the particle size can improve the particle engulfment during solidification [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling a kinetics equation necessitates a better understanding of the dynamic softening during hot deformation (simultaneous with straining) and the metadynamic or static softening between thermomechanical passes [3][4][5][6]. The modeling results are critical for the optimization of process parameters [7]. Generally, the degree of dynamic softening can be determined using relative softening (RS) or quasistatic softening, and four different methods, including offset-stress, back-extrapolation…”
Section: Introductionmentioning
confidence: 99%
“…Free-fall atomizer is less problematic than close-coupled atomizer in terms of thermal freezing since the melt stream and the gas jet are well separated at the exit of the melt from the delivery tube tip. The schematic sketch and details of free fall atomizer is shown in the Baolong zheng et al [8] studied the effect of gas composition on cooling rate of liquid drople. The results showed that the cooling rate of droplets increases with decreasing powder size and can achieve in excess of 10 5 K/s for powder <20 µm in diameter.…”
Section: Introductionmentioning
confidence: 99%